First interobserver agreement of optical coherence tomography in the bile duct: A multicenter collaborative study - Tyberg, Amy; Raijman, Isaac; Gaidhane, Monica; Trindade, Arvind J.; Shahid, Haroon; Sarkar, Avik; Samarasena, Jason; Andalib, Iman; Diehl, David L.; Pleskow, Douglas K.; Woods, Kevin E.; Gordon, Stuart R.; Pannala, Rahul; Kedia, Prashant; Draganov, Peter V.; Tarnasky, Paul R.; Sejpal, Divyesh V.; Kumta, Nikhil A.; Parasher, Gulshan; Adler, Douglas G.; Patel, Kalpesh; Yang, Dennis; Siddiqui, Uzma; Kahaleh, Michel; Joshi, Viren (Endoscopy International Open, 2022)
Background and study aims Optical coherence tomography (OCT) is a new technology available for evaluation of indeterminate biliary strictures. It allows under-the-surface visualization and preliminary studies have confirmed standardized characteristics associated with malignancy. The aim of this study is to evaluate the first interobserver agreement in identifying previously agreed upon OCT criteria and diagnosing of malignant versus benign disease. Patients and methods Fourteen endoscopists were asked to review an atlas of reference clips and images of eight criteria derived from expert consensus A total of 35 de-identified video clips were then evaluated for presence of the eight criteria and for final diagnosis of malignant versus benign using the atlas as reference Intraclass correlation (ICC) analysis was done to evaluate interrater agreement.Results Clips of 23 malignant lesions and 12 benign lesions were scored. Excellent interobserver agreement was seen with dilated hypo-reflective structures (0.85) and layering effacement (0.89); hyper-glandular mucosa (0.76), intact layering (0.81), and onion-skin layering (0.77); fair agreement was seen with scalloping (0.58), and thickened epithelium (0.4); poor agreement was seen with hyper-reflective surface (0.36). The diagnostic ICC for both neoplastic (0.8) and non-neoplastic (0.8) was excellent interobserver agreement. The overall diagnostic accuracy was 51 %, ranging from 43 % to 60 %. Conclusions Biliary OCT is a promising new modality for evaluation of indeterminate biliary strictures. Interobserver agreement ranged from fair to almost perfect on eight previously identified criteria. Interobserver agreement for malignancy diagnosis was substantial (0.8). Further studies are needed to validate this data.